PENGEMBANGAN KEWIRAUSAHAAN BERORIENTASI KEILMUAN DAN POTENSI LOKAL BAGI MAHASISWA UNIVERSITAS MULAWARMAN UNTUK MENGHASILKAN WIRAUSAHA YANG HANDAL, MANDIRI DAN PROFESSIONAL - Rudy Agung Nugroho; Jawatir Pardosi; Julinda Romauli Manullang; Andi Asikin Noor (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2019)
Many efforts have been made to increase entrepreneurship mental in higher education level so that students are interested to be entrepreneurs. This need to be done since the number of entrepreneurs in Indonesia is still limited. The Objective of this Entrepreneurship Development Program (EDP) was that to develop entrepreneurship at Mulawarman University which focused on local based content. This was done in order to bear professional, independent, and reliable entrepreneurs. To achieve the goals, this EDP socialized its program to all Faculties and Departments before conducting tenant open recruitment. Next, the selected tenants got training from experts. The training activities covered basic knowledge and practice of entrepreneurship and field trip to some local industries, which were considered to be successful. Afterward, the trainers were allowed to join internship program. In this program, trainers got expert assistance to help them to construct entrepreneurship proposal which was related to their field of study. When these targeted tenant had successfully run their small businesses professionally and independently, the new tenant were recruited in the next following year. By doing so, the cycles of entrepreneurship in Mulawarman University would continue to generate.